2016
DOI: 10.1002/mmce.20993
|View full text |Cite
|
Sign up to set email alerts
|

Broadband planar dipole array Antenna with double C-shaped slit elements for digital TV broadcasting transmission

Abstract: This research has proposed a planar rectangular dipole antenna enclosed in double C-shaped parasitically slit elements (i.e., radiator element) on a double-cornered reflector for bandwidth enhancement. In the study, simulations were first carried out to determine the optimal parameters of the radiator element and then a radiator element prototype was fabricated and mounted onto a double-cornered aluminum reflector. The simulated and measured |S 11 |<-10 dB of the antenna element covered the frequency ranges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…These works have well confirmed that the multi‐resonant concept should exhibit good robusty and potential for antenna designs in extremely critical installing environments, like all‐metal mobile handsets, or other compact consumer electronic devices. More recently, multi‐resonant dipole antenna array for digital TV transmission has been developed by using dipoles loaded with parasitic C‐shaped elements …”
Section: Applications and Discussionmentioning
confidence: 99%
“…These works have well confirmed that the multi‐resonant concept should exhibit good robusty and potential for antenna designs in extremely critical installing environments, like all‐metal mobile handsets, or other compact consumer electronic devices. More recently, multi‐resonant dipole antenna array for digital TV transmission has been developed by using dipoles loaded with parasitic C‐shaped elements …”
Section: Applications and Discussionmentioning
confidence: 99%